Assessment of Perfusion Abnormalities in a Case of Autism Spectrum Disorders Using 99mTc ECD Brain SPECT: A Landmark case in Bangladesh (Bangladesh Journal of Nuclear Medicine, 2024)
The prevalence of Autism Spectrum Disorders (ASD) has witnessed a rapid increase globally, necessitating effective diagnostic tools for comprehensive assessment. This case report presents a three-year-old male child clinically identified with ASD, undergoing a brain perfusion scan using single-photon emission computed tomography (SPECT). Hypoperfusion, characterized by multiple focal areas of decreased radiotracer concentration, was observed in frontal lobes, left temporal lobe, right parietal, right precuneus, and both hypothalami. The application of the e-ZIS system indicated a severity of rCBF decrease in specific voxels. This case underscores the utility of radionuclide brain SPECT imaging in unveiling abnormal rCBF patterns in ASD patients. Establishing a correlation between these abnormalities and symptom profiles could enhance treatment strategies, incorporating innovative interventions and specific medications tailored to the observed abnormalities.Bangladesh J. Nuclear Med. 27(1): 130-133, 2024